Decision making on detection and triage of oral mucosa lesions in community dental practices: screening decisions and referral. Issue 4 (25th January 2014) - Laronde, Denise M.; Williams, P. M.; Hislop, T. G.; Poh, Catherine; Ng, Samson; Zhang, Lewei; Rosin, Miriam P.
Abstract Oral cancer is a substantial, often unrecognized issue globally, with close to 300 000 new cases reported annually. It is a management conundrum: a cancer site that is easily examined; yet more than 40% of oral cancers are diagnosed at a late stage when prognosis is poor and treatment can be devastating. Opportunistic screening within the dental office could lead to earlier diagnosis and intervention with improved survival. Objective To describe how clinicians make decisions about referral based on the risk classification of the lesion. Methods Eighteen dentists from 15 dental offices participated in a 1‐day workshop on oral cancer screening. Participants then screened patients (medical history, conventional oral exam, fluorescent visualization examination) in‐office for 11 months, triaging patients by apparent clinical risk: low risk (common benign conditions, geographic tongue, candidiasis, trauma), intermediate risk (lichenoid lesions) and high risk (white or red lesions or ulcers without apparent cause). Clinicians made the decision on which lesions to reassess in 3 weeks based on risk assessment and clinical judgment. Lesions of concern were seen by a community facilitator or referred to an oral medicine specialist. Results Of 2542 patients were screened, and 389 lesions were identified (15% of patients). 350 were determined to be low risk (90%), 19 intermediate risk (IR) (5%), and 20 high risk (HR) (5%). One hundred and sixty‐six (43%) patients were recalled for 3‐week reassessment: 90% of HR lesions, 63% of IR lesions (63%), and 39% of low‐risk lesions. Compliance to recall was high (92% of cases). Reassessment eliminated the referral of 99/166 (60%) of lesions that had resolved. six lesions were biopsied with three low‐grade dysplasias identified. Conclusions Three key decision points were tested: risk assessment, need for reassessment, and need for referral. A 3‐week reassessment appointment was invaluable to prevent the unnecessary referral due to confounders. There is a need for a well‐defined triage pathway to facilitate oral cancer screening and a methodical and consistent approach to opportunistic screening in the dental office.